The Characteristics and Outcomes of Cardiopulmonary Resuscitation within the Neonatal Intensive Care Unit Based on Gestational Age and Unit Level of Care - Ahmad, Kaashif A.; Velasquez, Steven G.; Kohlleppel, Katy L.; Henderson, Cody L.; Stine, Christina N.; LeVan, Jaclyn M.; Bhalala, Utpal S. (American Journal of Perinatology, 2019)
Objectives This study aimed to describe the variation of in-neonatal intensive care unit (NICU) cardiopulmonary resuscitation (CPR) characteristics and outcomes across different gestational ages and levels of NICU care.Study Design This is a retrospective cohort study of in-NICU CPR events across 10 NICUs in San Antonio, TX from 2012 through 2017.Results We identified 140 patients experiencing a total of 210 in-NICU CPR events. CPR was performed in 0.23% of Level III and 0.85% of Level IV NICU admissions. Gestational age was inversely related to CPR incidence. The median age at in-NICU CPR was lower for preterm versus term infants (6 vs. 28 days, p = 0.002). With regression modeling, each added minute of chest compression decreased the odds of return to spontaneous circulation by 11%.Conclusion In-NICU CPR incidence rises with decreasing gestational age and increasing level of NICU care. The rate of return of spontaneous circulation decreases significantly with increasing duration of chest compressions. Further study is needed to identify patient factors associated with adverse outcome.
Keywords: cardiopulmonary resuscitation; level of care; gestational age